Perceptions and attitudes toward eco-toilet systems in rural areas: A case study in the Philippines - Ignacio, Jonathan Jared J. (Animo Repository, 2018)
© 2018 by the authors. Death due to diseases from poor sanitation is a serious global issue and it has become one of the priorities of the United Nations' Sustainable Development Goals (i.e., SDG6). This SDG6 aims to provide adequate improved sanitation facilities to over 2.3 billion people around the world who have no or limited access to sanitation, wherein more than two-thirds of these un-served people live in rural areas. One of the strategies for addressing this global issue is through emerging sustainable sanitation technologies such as the Eco-Toilet System (ETS), which uses small amounts of water or is even waterless and recovers nutrients from human waste thereby promoting water-energy conservation, improved sanitation and supplement nutrients essential to plant growth. Social acceptance, however, remains a key barrier in deploying the ETS. A social perception study on the use of the ETS was conducted in a rural community in Mulanay, Philippines. The researchers analyzed the proposed combined technology acceptance model and theory of planned behavior (C-TAM-TPB) using multiple linear regression and the Mann-Whitney U-test to evaluate the perceptions and attitudes of a rural community towards the use of the ETS. The results showed that more than 50% of the respondents are aware of the nutrient value of human excreta and believe that it is usable as fertilizer; however, less than 25% prefer to utilize it for food production. Results also indicate that the behavior of the users is driven by their attitude (β = 0.420, p-value < 0.010). Moreover, the Mann-Whitney U-test results revealed that people who are knowledgeable of the nutrient value of human excreta and are willing to collect them have more positive attitude towards the ETS.